The glaciogenic origin of the Pleistocene calcareous dust in Argentina on the basis of field, mineralogical, textural, and geochemical analyses. Issue 1 (30th August 2018) - Vogt, Thea; Clauer, Norbert; Techer, Isabelle
Abstract: Calcareous dust occurs in Argentina as layers and pockets closely associated with Pleistocene deposits and periglacial features from southernmost Patagonia to at least the Mendoza Precordillera and has been traditionally interpreted as a soil horizon resulting from postdepositional pedogenesis during interglacials. Detailed field and microscopic observations and sedimentological and geochemical analyses of more than 100 samples collected from lower to upper Pleistocene deposits between 51°S and 33°S and from near sea level to 2800 m asl allow us to interpret the dust as synchronous with the host sediment. All observations and analyses lead us to conclude that: (1) the cryogenic morphology and the chemical signatures of the calcite component show that the dust is glaciogenic, (2) the dust was carried by southeasterly Antarctic winds, and (3) it was deposited over most of southern and central Argentina. Field observations, geomorphic evidence, and radiocarbon dates suggest that the dust was deposited during several Pleistocene glacial episodes.